Gene regulation by nucleoporins and links to cancer - Köhler, Alwin; Hurt, Ed (Molecular cell, 2010)
Nuclear pore complexes (NPCs) composed of ∼30 individual nucleoporins form huge macromolecular assemblies in the nuclear envelope, through which bidirectional cargo movement between the nucleus and cytoplasm occurs. Beyond their transport function, NPCs can serve as docking sites for chromatin and thereby contribute to the organization of the overall topology of chromosomes in conjunction with other factors of the nuclear envelope. Recent studies suggest that gene-NPC interactions may promote both transcription and the definition of heterochromatin-euchromatin boundaries. Intriguingly, several nucleoporins were linked to cancer, mostly in the context of chromosomal translocations, which encode nucleoporin chimeras. An emerging concept is that tumor cells exploit specific properties of nucleoporins to deregulate transcription, chromatin boundaries, and essential transport-dependent regulatory circuits. This review outlines new mechanistic links between nucleoporin function and cancer pathogenesis.